Penggunaan Model Steam (Science, Techonology, Engineering, Art, And Mathematics ) Pada Pembelajaran IPA Untuk Meningkatan Prestasi Belajar Peserta Didik Di Kelas V A SD Negeri 2 Loloan Barat: The Use Of Steam Model (Science, Technology, Engineering, Art, And Mathematics) In Science Learning To Improve Student Achievement In Class Va Sd Negeri 2 Loloan Barat - Hidayah, Niki; Prayogo, Muhammad Suwignyo (Pendidikan Islam Pascasarjana IAIN Jember, 2022)
The low learning achievement of students, particularly in science learning, is the background of this study. This study uses the STEAM (science, technology, engineering, art, and mathematics) model to enhance students' learning achievement in science. The research method employed is called Classroom Action Research (CAR), and it is carried out in cycle II with two sessions per cycle utilizing the Kemmis and McTaggart approach. The planning, carrying out, observing, and reflecting phases make up this research. Students in class VA SD Negeri 2 Loloan Barat are the study's participants. comprising 19 students in all, 13 boys, and 6 girls. An evaluation sheet with exam questions, student activity observation sheets, and teacher activity observation sheets are employed as the data gathering tools. Each cycle shows the effects of the increase. The student activities in the first cycle received an average score of 54.43% with fewer requirements, while cycle II received an average of 81.04% with extremely strong requirements. Students in the first cycle of science learning received an average grade of 66.99, a completeness rating of 53.94, and fewer criteria. The second cycle's students' learning achievement averaged 80.34 with a very good criteria completeness percentage of 82.35%.The STEAM learning paradigm (science, technology, engineering, art, and mathematics) can enhance students' learning achievement in science for class VA at SD Negeri 2 Loloan Barat, according to the findings of the analysis of the research data..